Определим значение следующего выражения. Записываем полученное решение.30 4/5 - 1 2/5 * (1 4/5 * (12 7/12 - 9 19/36) - 17/35 * 1 11/34) = 30 4/5 - 7/5 * (9/5 * (151/12 - 343/36) - 17/35 * 45/34) = 30 4/5 - 7/5 * (9/5 * (453/36 - 343/36) - 17/7 * 9/34) = 30 4/5 - 7/5 * (9/5 * 110/36) - 17/7 * 9/34) = 30 4/5 - 7/5 * (1/5 * 110/4) - 1/7 * 9/2) = 30 4/5 - 7/5 * (22/4 - 9/14) = 30 4/5 - 7/5 * (11/2 - 9/14) = 30 4/5 - 7/5 * (77/14 - 9/14) = 30 4/5 - 7/5 * 68/14 = 30 4/5 - 1/5 * 68/2 = 30 4/5 - 1/5 * 34 = 154/5 - 34/5 = 120/5 = 24.В результате получается ответ равный 24.